Children of AIDS : Africa's orphan crisis - Guest, Emma, 1970- (London ; Sterling, Va. : Pluto Press ; Pietermaritzburg, South Africa : University of Natal Press, 2003)
'This brave and moving book forces us to open our eyes to the full extent of the devastation that AIDS is causing in Africa. Through the words of AIDS orphans and those struggling to cope with the flood of unwanted children, Children of AIDS serves as a wake-up call for the international community.' Susan Sarandon'An important and timely book on a devastating crisis.' Fergal Keane'Guest compresses her research on this enormously explosive crisis into a short and tightly structured book ... Her book will help to give a fuller understanding of the orphan crisis.' The Sunday Independent, South Africa'The author, a perceptive analyst of the ongoing AIDS tragedy, presents case studies of organized responses in three countries hit hard by the epidemic: Uganda, Zambia and South Africa. By exploring the social reality behind the numbing statistics, she makes possible more informed speculation about the economic, social and psychological impact of the disease in coming decades.' Foreign AffairsThis is the new, fully updated, first paperback edition of Emma Guest's acclaimed book that explores how the AIDs crisis has devastated the world's poorest continent, and shows how families, charities and governments are responding to the next wave of the crisis - millions of orphans. Based on extensive interviews, Guest lets people tell their own stories in their own words. The result is a moving and disturbing account of the experiences of orphans, street children, grandparents, aunts, foster parents, charity and social workers and foreign donors across South Africa, Zambia and Uganda.
Mbuya's Story: A Grandmother's Story, Lusaka, Zambia -- Extended Families: An Aunt's Story, Kampala, Uganda -- Strangers Step in: The Tale of Two Foster Parents, South Africa -- Childcare by Committee: A Social Worker's Story, Pietermaritzburg, South Africa -- Hope in the Hills: 'Clustering Fostering' in Rural KwaZulu-Natal, South Africa -- Institutionalised: An Orphanage in Cape Town, South Africa -- A Hundred Dollars for a Bull: A Social Worker's Story, Luweero District, Uganda -- Foreign Aid or Interference? United Nations Children's Fund (UNICEF), Lusaka, Zambia -- A Mother to Her Brothers: A Child-headed Household's Story, Johannesburg, South Africa -- Falling Through the Net: A Street Child's Story, Lusaka, Zambia.
Includes bibliographical references (pages 167-168) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Orphans -- Services for -- Africa; Children of AIDS patients -- Services for -- Africa; AIDS (Disease) -- Social aspects -- Africa; Social problems; Africa; Child Welfare; Foster Home Care; Financing, Government; Social Problems; Africa; Enfants de sidéens -- Services -- Afrique; Sida -- Aspect social -- Afrique; Aide de l'État.; Problèmes sociaux; Afrique; federal aid; social issues; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; SOCIAL SCIENCE -- Disease & Health Issues; Social problems; AIDS (Disease) -- Social aspects; Children of AIDS patients -- Services for; Orphans -- Services for; Africa; HIV/AIDS.; Soziale Probleme; Waisenkind; Subsaharisches Afrika; Aids